Numerical investigation of novel dynamic installed fish anchors in clay and calcareous silt. (1st September 2018) - Kim, Y.H.; Hossain, M.S.; Chang, K.
Abstract: This paper reports the results from three-dimensional dynamic finite element analysis undertaken to provide insight into the behaviour of a novel dynamically installed anchor (DIA), termed as fish DIA, during dynamic installation and monotonic pullout in non-homogeneous clay and calcareous silt. The fish DIA has an elliptic-shaped shaft, which reduces hydrodynamic drag resistance. The shaft is shaped to be thicker near the head to lower the mass centroid, and increase its diving potential with a specialised padeye position. A series of large deformation finite element analyses have been carried out considering the relevant range of parameters in terms of soil undrained shear strength; impact velocity, padeye offset ratio and pullout angle. Considering the difference in soil undrained shear strength, and DIA dimensions and mass; overall anchor tip embedment depths of the fish DIA lied in the range of that of the OMNI-Max DIA. The tracked anchor trajectory confirmed that, compared to the OMNI-Max DIA, the fish DIA dove deeper and earlier for a wide range of padeye offset ratio. These are more critical and beneficial for calcareous silt where the achieved embedment depths are generally lower compared to those in clay. Highlights: New dynamically installed anchor (DIA) shape, termed as fish DIA. Soil failure patterns: (a) dynamic installation; (b) monotonic pullout. Extensive parametric investigation: (a) soil type; (b) impact velocity (c) pullout angle; (d) padeye offset ratio. Fish DIA dove deeper and earlier for a wide range of padeye offset ratio, compared to existing DIA. For assessing embedment depth and diving potential of DIAs, improved rational design approaches were proposed.